Driving to communicative approach: the innovative teaching speaking methods in Indonesian English immersion program - Widya Rizky Pratiwi; Heri Kuswoyo; Maya Puspitasari; Juhana Juhana; Bachtiar Bachtiar (International Journal of Evaluation and Research in Education (IJERE), 2024)
Students’ failure to be successful English learners is primarily due to uninteresting materials that lead to demotivation in learning. This research aimed to uncover the students’ motivation to study in the Indonesian English immersion program (IEIP) of Kampung Inggris Pare and to investigate the innovative methods of teaching speaking as a communicative approach in the IEIP at Kampung Inggris Pare. This qualitative study with a micro-ethnography approach was conducted in four English course institutions by associating ten students and four teachers as participants. By having the initial interviews, the results revealed that most students perceived learning English at formal schools as unsatisfied. In comparison, the two months of observation in “the daffodils, Mr. Bob, Kresna, and Peace” English course institutions found that the teachers taught speaking by integrating the other skills and utilizing some sources. They could regulate and deliver the materials attractively based on their methods. The communicative methods employed namely teaching speaking through writing practice (TSWP), teaching speaking through listening practice (TSLP), and teaching speaking through visual media or pictures (TSVM). This study supports students learning English at the IEIP because it fits the purpose of communicative goals, which directs the students’ success.